Advances in Thermionic Energy Conversion through Single-Crystal n-Type Diamond - Koeck, Franz A. M.; Nemanich, Robert J. (Frontiers in Mechanical Engineering, 2017)
Thermionic energy conversion, a process that allows direct transformation of thermal to electrical energy, presents a means of efficient electrical power generation as the hot and cold side of the corresponding heat engine are separated by a vacuum gap. Conversion efficiencies approaching those of the Carnot cycle are possible if material parameters of the active elements at the converter, i.e. electron emitter or cathode and collector or anode, are optimized for operation in the desired temperature range. These parameters can be defined through the law of Richardson-Dushman that quantifies the ability of a material to release an electron current at a certain temperature as a function of the emission barrier or work function and the emission or Richardson constant. Engineering materials to defined parameter values presents the key challenge in constructing practical thermionic converters. The elevated temperature regime of operation presents a constraint that eliminates most semiconductors and identifies diamond, a wide band-gap semiconductor, as a suitable thermionic material through its unique material properties. For its surface a configuration can be established, the negative electron affinity (NEA), that shifts the vacuum level below the conduction band minimum eliminating the surface barrier for electron emission. In addition, its ability to accept impurities as donor states allows materials engineering to control the work function and the emission constant. Single crystal diamond electrodes with nitrogen levels at 1.7 eV and phosphorus levels at 0.6 eV were prepared by plasma enhanced chemical vapor deposition where the work function was controlled from 2.88 eV to 0.67 eV, one of the lowest thermionic work functions reported. This work function range was achieved through control of the doping concentration where a relation to the amount of band bending emerged. Upward band bending that contributed to the work function was attributed to surface states where lower doped homoepitaxial films exhibited a surface state density of ~3x1011 cm-2. With these optimized doped diamond electrodes highly efficient thermionic converters are feasible with a Schottky barrier at the diamond collector contact mitigated through operation at elevated temperatures.